The Relationship of Genetic Polymorphism Micromal Epoxide Hydrolase (EPHX1) His139Arg and Lung Cancer - Rosidah Hanum Hasibuan; Noni Novisari Soeroso; Setia Putra Tarigan; Yahwardiah Siregar; Erna Mutiara; Lucia Aktalina (Jurnal Respirologi Indonesia, 2022)
Background: Microsomal epoxide hydrolase 1 (EPHX1) plays an important role in both activation and detoxification of polycyclic aromatic hydrocarbons (PAH) and aromatic amines. Polymorphism EPHX1 His139Arg in susceptibility to lung cancer has been reported with inconsistent outcomes. Aim of this study was to analyze the relationship between this polymorphism and lung cancer in smokers.Method: Consecutive sampling and case-control study was applied. Genotyping was performed by PCR-RFLP assay. The chi-square test with p<0.05 considered as significant.Results: Of all 84 subjects, in case and control groups, wild-type variant His139His were 34 (81%) and 30 (71.4%), heterozygote variant His139Arg were 8 (19%) and 12 (28.6%), there was no homozygote variant Arg139Arg identified. (p=0.36).Conclusion: The EPHX1 His139His represents a common polymorphism in both of subject groups. There is no association between His139Arg polymorphism of EPHX1 and lung cancer.